التأويل فى المعتقدات عند السلفيين - Musawar Musawar (Universitas Islam Negeri Mataram, 2014)
There are some verses of the holy Qur’an, so called as āyāt mutashābihāt, whose meanings have been revealing conflict of opinions and controversies among the Muslims. To understand such verses ‘ulamā’ apply ta’wīl. Unfortunately, its use is not necessarily accepted by all ‘ulamā’; some accept and some reject it. The level of acceptance is also varies from unrestricted to moderate and very strict way of using. It is so in the level of rejection that varies from fully rejecting it to partially rejecting it with certain tight exception. This article is aimed at analyzing the Salafi’s views on using ta’wīl to understand āyāt mutashābihāt; whether they are liberal or moderate or fully reject it. It is found that the Salafis refuse using ta’wīl, because they consider it heresy, and it will lead to ta‘ṭīl (discarding the original meaning).